2004
DOI: 10.1016/s0002-9440(10)63760-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Regulation of Estrogen Receptor-β Expression by DNA Methylation During Prostate Cancer Development and Metastasis

Abstract: Estrogen receptor (ER)-beta is thought to exert anti-proliferative effects in the normal prostate but supports prostate cancer (PCa) cell survival. We previously reported that the receptor's expression declined as PCa developed in the gland but reappeared in lymph node and bone metastases. To investigate whether hypermethylation was the underlying mechanism for these phenomena, we first identified two CpG islands (CGIs) encompassing 41 CpG dinucleotides, located separately in the untranslated exon 0N and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
179
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(198 citation statements)
references
References 30 publications
17
179
2
Order By: Relevance
“…We propose that ER-b may have a role in tissue repair and healing after radiation therapy. Although most authors describe low levels of ER-b expression in LNCaP, in some studies, including our current results and a recent study by Zhu et al 40 no mRNA levels could be detected. Zhu et al 40 actually demonstrated that this lack or low expression of ER-b in LNCaP is the result of epigenetic silencing and found a progressive decrease in ER-b gene expression from early passages (<7 passages) to high passages (>25 passages).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…We propose that ER-b may have a role in tissue repair and healing after radiation therapy. Although most authors describe low levels of ER-b expression in LNCaP, in some studies, including our current results and a recent study by Zhu et al 40 no mRNA levels could be detected. Zhu et al 40 actually demonstrated that this lack or low expression of ER-b in LNCaP is the result of epigenetic silencing and found a progressive decrease in ER-b gene expression from early passages (<7 passages) to high passages (>25 passages).…”
Section: Discussioncontrasting
confidence: 77%
“…Although most authors describe low levels of ER-b expression in LNCaP, in some studies, including our current results and a recent study by Zhu et al 40 no mRNA levels could be detected. Zhu et al 40 actually demonstrated that this lack or low expression of ER-b in LNCaP is the result of epigenetic silencing and found a progressive decrease in ER-b gene expression from early passages (<7 passages) to high passages (>25 passages). In addition to the number of passages, some other variation in culture conditions may be responsible, but variation in the sensitivity of RT-PCR studies should not be excluded a priori.…”
Section: Discussioncontrasting
confidence: 77%
“…No information is available about how ERb is regulated in PCa cells except for our recent study suggesting that changes of ERb expression during prostate carcinogenesis in vivo could be regulated by DNA methylation (Zhu et al, 2004). In this study, we identified one composite CpG island (CGI) spanning the proximal promoter and the untranslated 0N exon of the ERb gene (Figure 1).…”
Section: Introductionmentioning
confidence: 73%
“…The relative position of the 46 CpG sites in the three methylation centers identified in our previous study (Zhu et al, 2004) are shown in Figure 1. We used the 0N-Luc (581 bp) as a template and performed serial-and center-specific deletions to characterize the role of the sequences in these methylation hotspots of the 0N promoter.…”
Section: Center 1 Is Crucial For Erb Expression In Pca Cellsmentioning
confidence: 94%
“…It contains a typical CpG island within its promoter (5), and has been shown to be re-expressed in prostate cancer cell-lines treated with DNMT inhibitors such as 5-aza-2'deoxycytidine (6)(7)(8). Furthermore, methylation-specific PCR studies have shown that the promoter region of the ERβ gene is hypermethylated in prostate cancer tissue studies (6,8,9). The loss of ERβ in prostate cancer cell-lines and in tissue studies adds to an accumulating body of evidence supporting an antiproliferative role for ERβ in the prostate.…”
Section: Introductionmentioning
confidence: 99%